Perbedaan Intensitas Komunikasi Melalui Jejaring Sosial antara Tipe Kepribadian Ekstrovert dan Introvert pada Remaja - Widiantari, Komang Sri; Herdiyanto, Yohanes Kartika (Program Studi Sarjana Psikologi, Fakultas Kedokteran, Universitas Udayana, 2013)
The progress of information and communication technology influencethe increase of the usage of social network. Social network users are mostly inadult group. The existence of social networks can bring positive impact as well as negative impact to the society especially in adult group. The aim of this research is to find out the difference in communication intensity through social networks between extrovert and introvert types of personality in adolescents. This research is a quantitative research with comparative method, the sampling technique used in this research is stratified proporsional randomsampling and the population is High School students in Denpasar, with the total respondents 218 student. The analysis data by t-test independent sample, and shown the result that there was a difference in the communication intensity through social network between introvert and extrovert type of personality in adolescents, the extrovert personality had a high level of communication better than introvert personality. The additional analysis, it is stated that there was a relationship between the number of social networks and the intensity of communication on social networks, and there was no difference in the intensity of communication based on gender. Keywords: Communication intensity, social networks, extrovert,introvert